Karakteristik Dan Model Pembelajaran Pai Bagi Anak Berkebutuhan Khusus (ABK) DI SLB/A Yaketunis - Muhammad Abduh; Krista Emilia; Ririn Nur Primaningrum; Difa Ul Husna (STIKes Ibnu Sina Ajibarang, 2024)
This research discusses the Characteristics and Model of PAI Learning for ABK at SLB/A Yaketunis. The method used is a qualitative method. The subject in this research is the main source that can provide the data information needed to support the problems in the research. The main source who is the subject of this research is the Islamic Religious Education Teacher. The data collection method uses observation and interviews using observations and recording important points in order to obtain data directly on the research object. The research results show that the PAI learning process at SLB/A Yaketunis was adapted through a music-based approach, by changing the learning material into songs that are sung during the learning process. Learning materials are also linked to students' daily activities to facilitate understanding and application of religious teachings in the context of their lives. Inclusive learning strategies are used to overcome the different speed of understanding of each MDVI student. Good collaboration between educators, students, and parents is important to understand students' individual needs and develop appropriate learning strategies.